(untitled) (Stamford Journal of Microbiology, 2015)
Infectious diseases caused by microbial pathogens are most common and widespread health risks are associated with drinking water. This paper presents a model for prediction of disease burden for ingestion of microbial pathogens through drinking water in rural Bangladesh. The concentration of indicator organisms (Thermotolerant coliform or Escherichia coli) in cfu/100ml were taken as input in the model and estimated disease burden in ?DALYs with some relevant statistical parameters are obtained as output. The model has been found useful in quantifying relative disease burden of microbial pathogens, comparing safety of different water supply options and delineating the interventions needed to reduce disease burden from drinking water. DOI: http://dx.doi.org/10.3329/sjm.v4i1.22759 Stamford Journal of Microbiology, Vol.4(1) 2014: 31-36